The Design of a Turbine Emulator for a Pico-Hydrokinetic Power Generation System - Ikhsan, Muhammad; Muazim, T. Alfi (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
Pico-Hydrokinetic Power Plants (PHKPP) utilize the kinetic energy of flowing water as a sustainable alternative to fossil-based energy. However, higher education remains largely theoretical due to limited laboratory facilities, restricted access, and inadequate simulation tools. This study develops a cost-effective PHKPP emulator to support experiential learning and represent real-world operating conditions. A quantitative approach is used, integrating the ADDIE model with experimental testing. The emulator consists of two independent units that simulate a turbine using a three-phase induction motor controlled by Variable Speed ​​Drives (VDRs), while power generation is achieved through a single-phase induction generator. Evaluation results indicate that the emulator effectively supports learning, enabling analysis of turbine performance, control strategies, and energy conversion efficiency. Student responses demonstrated a high level of acceptance, with an average score of 4.43 across all aspects of functionality, usability, relevance, and design. These findings confirm that the emulator effectively enhances conceptual understanding and is an appropriate learning solution for PHKPP learning